the sorcerer's code. - hutson, matthew (Psychology Today)
The article discusses the author's conversation with Richard Stallman, a computer programmer who established a free software (FS) movement in large to address his own concerns about digital privacy and the future of information sharing. Topics mentioned include the difference between FS and proprietary software, open source software, and the creation of the free operating system GNU. Also explored are Stallman's way of life and character.